The use of ultrasound improves the accuracy of epidural needle placement in cadavers - Keßler, Jens; Moriggl, Bernhard; Grau, Thomas (Surgical and radiologic anatomy. [Englische Ausgabe], 2014)
To investigate whether epidural-prepuncture ultrasound imaging improves the accuracy and quality of epidural needle placement or not?